Representation of Women in Sufism Literature: A Comparative Study of the Thought of Rabī'ah al-'Adawiyah and Sa'diyya Shaikh - Galang Prayoga; Ginanjar Fernando; Ahmad Sardana; Mujiburrahman Mujiburrahman; Raja Mahendra Nagari (Arba: Jurnal Studi Keislaman, 2026)
The study of Sufism in the Islamic tradition is often dominated by an androcentric perspective that places women’s spiritual experiences as peripheral and subordinate, thus obscuring women’s position as autonomous religious subjects. The lack of comparative studies across periods that dialogue classical female Sufi figures with contemporary feminist Sufi thinkers indicates a significant research gap in the study of Sufism and gender. This study aims to comparatively analyze the representation of women in Sufism through the figure of Rabīʻah al-ʻAdawiyah and the Sufi-feminist thought of Sa’diyya Shaikh, and formulate its theoretical implications for the development of a gender-just Sufi epistemology. The study employs qualitative methods with a comparative-hermeneutical approach, utilizing textual analysis of primary and secondary sources, including classical Sufi hagiography, Sufi works, and contemporary writings by Sa’diyya Shaikh, within a critical and feminist hermeneutic framework. The results of the study show that Rabīʻah al-ʻAdawiyah represents women as independent spiritual subjects through the concept of maḥabbah Ilāhiyyah, which rejects transactional relations between humans and God and transcends gender categories and social hierarchies. Meanwhile, Sa’diyya Shaikh reconstructs Sufism as a space of liberating ethics through the hermeneutics of spiritual justice, by emphasizing the egalitarian relationship between God and humans as the basis for gender equality. A comparative analysis reveals the continuity of spiritual values, as well as differences in epistemic strategies, in responding to patriarchal structures across various historical contexts. This study concludes that the synthesis of both thoughts offers an inclusive Sufism paradigm that emphasizes women’s contributions in the formation of Islamic spiritual epistemology and broadens the horizon of contemporary Sufism studies that are gender-just.